IMPLEMENTASI SISTEM PEMANTAUAN KUALITAS UDARA REAL-TIME BERBASIS IOT PADA PABRIK KIPAS (STUDI KASUS: BY KIPAS BALI) - I Wayan Gova Prapta Abiantara; Made Adi Paramartha Putra; Ni Putu Noviyanti Kusuma (INTECOMS: Journal of Information Technology and Computer Science, 2026)
The wooden fan production process at By Kipas Bali generates fine dust, fumes, and VOC emissions from cutting, sanding, and painting activities, which can degrade indoor air quality. To address the absence of a real-time monitoring system, this study develops an IoT-based air quality monitoring prototype using MQ135 and DHT22 sensors, an ESP32 microcontroller, and a Firebase-powered web dashboard. The prototype method is applied through stages of planning, design, construction, and testing. Two MQ135 sensors are installed at different production points to obtain more representative pollutant readings, while DHT22 measures temperature and humidity. Sensor data is processed by ESP32, transmitted to Firebase, and visualized in real time on a web dashboard. A buzzer provides immediate warnings when pollutant levels exceed safety thresholds. The system successfully delivers real-time monitoring, responsive alerts, and reliable data visualization, supporting safer and more controlled working conditions in the factory environment.